2011
DOI: 10.1186/1752-1947-5-79
|View full text |Cite
|
Sign up to set email alerts
|

Occult renal cell carcinoma manifesting with epistaxis in a woman: a case report

Abstract: IntroductionMetastatic disease in the sinonasal region occurs rarely and the primary site may be elusive. This case highlights the possibility of an occult renal tumor manifesting with nasal symptoms and the risk of severe bleeding following nasal biopsy.Case presentationWe report the case of a 79-year-old Caucasian woman who presented with a six-week history of intermittent left-sided nosebleeds. She was fit, without previous surgery or anticoagulation. Nasal endoscopy and computed tomography showed a hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…RCC can metastasize early, and symptoms of a metastatic tumor may be the first clinical presentation . Alternatively, sinonasal RCC metastases may occur many years (up to 18) after treatment of the primary tumor .…”
Section: Primary Tumor Sitesmentioning
confidence: 99%
“…RCC can metastasize early, and symptoms of a metastatic tumor may be the first clinical presentation . Alternatively, sinonasal RCC metastases may occur many years (up to 18) after treatment of the primary tumor .…”
Section: Primary Tumor Sitesmentioning
confidence: 99%
“…Bernstein et al, reported that a breast malignancy was the third most common cause for metastasis to the paranasal sinuses; the most common source is a renal primary. This has been confirmed in subsequent reviews of the literature [4, 6]. …”
Section: Discussionsupporting
confidence: 71%
“…Metastases to the ethmoid sinuses are rarer still, with only three documented cases from a breast primary [3, 4]. The most common site within the paranasal sinuses for breast cancer metastases is the maxilla/maxillary antrum [3, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, possibility of a primary or secondary maxillary tumor must be considered in case of ineffective sinus infection treatment (7)(8)(9)(10).…”
mentioning
confidence: 99%